Characterization of Residual Stresses Induced into Bearing Rings by Means of Turning in Soft State Using Different Turning Parameters - Jawad Zaghal; Valeria Mertinger; Adam Filep; Gyula Varga; Marton Benke (Journal of Machine Engineering)
Residual stresses remain in solid materials after removing the external load. The residual stresses which are induced by machining processes play important role in determining the service life of machined components, depending on their magnitude, sign, and direction. This research provides a comprehensive correlation between three turning parameters and the resulted residual stresses formed on the surface of the outer ring of tapered roller needle bearing, made of 100CrMnSi6-4 type steel. The examined parameters are turning speed, feed, and tool nose radius. Radial and axial residual stresses on the surface were measured using sample cutting-free X-ray diffraction method. It is shown that the effect of one processing parameter can even be opposing depending on the other parameters. Thus, the effects of turning parameters on residual stresses must be examined in a comprehensive manner.